Bernard Shaw on the American Stage A Chronicle of Premieres and Notable Revivals - Conolly, L. W. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Bernard Shaw on the American Stage is the first comprehensive study of the production of Bernard Shaw's plays in America. During his lifetime (1856-1950), Shaw was America's most popular living playwright; productions of his plays were outnumbered only by Shakespeare. Forty-four of Shaw's plays were staged in America before his death, eight more posthumously. Eleven of the productions were world premieres. Bernard Shaw on the American Stage tells the story of the fifty-two premieres, which, apart from a few fragments, is his total dramatic oeuvre. The book also includes, again for the first time, production data and concise overviews of dozens of the most notable American revivals of the plays, from the 1890s to the beginning of the 2020 pandemic. Illustrations-production photographs, programmes, theatre buildings, playbills, actors' studio portraits- inform the study throughout. L. W. Conolly is Emeritus Professor of English at Trent University, Canada, and Resident Scholar of The Shaw Festival, Ontario. He is also Literary Adviser to the Shaw Estate, a Senior Fellow of Massey College, University of Toronto, an Honorary Fellow of Robinson College, University of Cambridge, a Fellow of the Royal Society of Canada, and former President of the International Shaw Society. Dr Conolly's previous publications on Shaw include, but are not limited to, critical editions of The Philanderer (2015), Pygmalion (2008), and Mrs Warren's Profession (2005), and studies such as Bernard Shaw: On Politics (2016), The Shaw Festival: The First Fifty Years (2011), Bernard Shaw and the BBC (2009), and Bernard Shaw and Barry Jackson (2002).
Chapter 1: The Mansfield Years -- Chapter 2: The Daly Years -- Chapter 3: Robert Loraine and Man and Superman -- Chapter 4: The Syndicates -- Chapter 5: Eliza Comes to Broadway -- Chapter 6: The War Years -- Chapter 7: The Little Theatres -- Chapter 8: The Theatre Guild -- Chapter 9: Political Shaw -- Chapter 10: Posthumous Shaw. .
Keywords: Theater-History.; Theater; Playwriting; Dramatists; Theater-Production and direction; Actors; Theatre History; Global and International Theatre and Performance; Playwrights and Playwriting; Theatre Direction and Production; Performers and Practitioners